ROS-mediated autophagy increases intracellular iron levels and ferroptosis by ferritin and transferrin receptor regulation - Park, Eunhee; Chung, Su Wol (Cell death & disease, 2019)
Ferroptosis is a novel form of programmed cell death in which the accumulation of intracellular iron promotes lipid peroxidation, leading to cell death. Recently, the induction of autophagy has been suggested during ferroptosis. However, this relationship between autophagy and ferroptosis is still controversial and the autophagy-inducing mediator remains unknown. In this study, we confirmed that autophagy is indeed induced by the ferroptosis inducer erastin. Furthermore, we show that autophagy leads to iron-dependent ferroptosis by degradation of ferritin and induction of transferrin receptor 1 (TfR1) expression, using wild-type and autophagy-deficient cells, BECN1 +/− and LC3B −/− . Consistently, autophagy deficiency caused depletion of intracellular iron and reduced lipid peroxidation, resulting in cell survival during erastin-induced ferroptosis. We further identified that autophagy was triggered by erastin-induced reactive oxygen species (ROS) in ferroptosis. These data provide evidence that ROS-induced autophagy is a key regulator of ferritin degradation and TfR1 expression during ferroptosis. Our study thus contributes toward our understanding of the ferroptotic processes and also helps resolve some of the controversies associated with this phenomenon.